Wykreślne Wyznaczanie Rozkładu Naprężeń przy Plastycznym Zginaniu Blach z Uwzględnieniem Siły Osiowej - Marciniak, Zm. (Engineering Transactions, 1958)
This paper contains a description of a method for determining the stress distribution in sheet strips in the direction of the thickness, during the process of wrapping them round a cylindrical body. It is assumed that the bending takes place with the simultaneous action of an axial force, causing a reduction in width and thickness of the strip. A geometrical interpretation of the relations obtained is given, using a system of three axes of coordinates, each pair of the coordinate axes comprising an angle of 120°. This method may be used for the graphical determination of the quantities required. Following the description of the principles of the graphical method, an example of application is given, in which the distribution of the three principal stresses in a cross-section of the strip is determined.